Effect of CAD/CAM Guide Plate Combined With Socket-Shield Technique in Immediate Implantation of Anterior Teeth Aesthetic Area and Its Influence on Aesthetics - Wang, Zhigang; Liu, Jianwei; Wang, Xinquan; Wang, Ning; Teng, Min (Frontiers in Surgery, 2022)
Purpose The purpose of this study is to discuss the effect of computer-aided design or computer-aided manufacturing (CAD/CAM) guide plate combined with socket-shield technique (SST) in immediate implantation of anterior teeth aesthetic area and its influence on aesthetics. Methods A total of 102 patients with immediate implantation in our hospital from March 2017 to March 2020 were selected. According to different repair methods, patients were divided into conventional group (n = 51) and observation group (n = 51). Traditional immediate implantation was performed in conventional group. The observation group underwent immediate implantation with CAD/CAM guides combined with SST. Immediately after operation and 12 months after operation, the success rate, implant deviation, periodontal index, absorption of labial bone plate, complications, aesthetic effects, and satisfaction of the two groups were observed. Results There was no significant difference in the success rate between the two groups (p > 0.05). The implant deviation values in the observation group were all lower than those in the conventional group (p < 0.05). PD, PLI, and SBI in the observation group were all lower than those in the conventional group (p < 0.05). The absorption value of labial bone plate in the observation group were all lower than those in the conventional group (p < 0.05). The total incidence of complications in the observation group (5.88%) was lower than that in the conventional group (19.61%) (p < 0.05). The PES and WES in the observation group were higher than those in the conventional group (p < 0.05). The total satisfaction in the observation group (92.16%) was higher than that in the conventional group (76.47%) (p < 0.05). Conclusion : The application of CAD/CAM guide plate combined with SST in immediate implantation of anterior teeth aesthetic area has a good effect, which can improve the accuracy of implantation, improve the periodontal environment, reduce bone resorption, reduce complications, improve aesthetics, and have high patient's satisfaction.